2012
DOI: 10.4103/0189-6725.93294
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a tubularised incised-plate urethroplasty with double de-epithelised dartos flaps in a failed hypospadias repair: A preliminary report

Abstract: The preliminary results showed that TIPU with double de-epithelised dartos flaps is a useful method of successfully repairing failed hypospadias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Neourethral tube length, suture technique, urinary diversion selection, stent use, surgical technique and anatomic features like distal urethral plate and glandular groove are known to affect the success of TIPU surgery. Currently, the surgical method has been modified to include transfer of tissue like dorsal or ventral‐lateral dartos fascia flap or corpus spongiosum flap over the neourethral tube to increase the success of surgery or reduce complication rates (Yildiz et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Neourethral tube length, suture technique, urinary diversion selection, stent use, surgical technique and anatomic features like distal urethral plate and glandular groove are known to affect the success of TIPU surgery. Currently, the surgical method has been modified to include transfer of tissue like dorsal or ventral‐lateral dartos fascia flap or corpus spongiosum flap over the neourethral tube to increase the success of surgery or reduce complication rates (Yildiz et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have reported that the use of the dartos flap is a good choice for preventing fistula [11,12]. Many studies have begun to use the double-dartos flap in order to prevent the total formation of the fistula for both primary and failed Hp repair [13,14,15,16]. In our study, we also applied double-dartos flaps using a prepucial flap by dividing the dorsal prepucial flap into two equal parts for primary cases (fig.…”
Section: Discussionmentioning
confidence: 99%